The under-reported role of toxic substance exposures in the COVID-19 pandemic (2020)
Coronavirus disease 2019 (COVID-19) and previous pandemics have been viewed almost exclusively as virology problems, with toxicology problems mostly being ignored. This perspective is not supported by the evolution of COVID-19, where the impact of real-life exposures to multiple toxic stressors degrading the immune system is followed by the SARS-CoV-2 virus exploiting the degraded immune system to trigger a chain of events ultimately leading to COVID-19. This immune system degradation from multiple toxic stressors (chemical, physical, biological, psychosocial stressors) means that attribution of serious consequences from COVID-19 should be made to the virus-toxic stressors nexus, not to any of the nexus constituents in isolation. The leading toxic stressors (identified in this study as contributing to COVID-19) are pervasive, contributing to myriad chronic diseases as well as immune system degradation. They increase the likelihood for comorbidities and mortality associated with COVID-19. For the short-term, tactical/reactive virology-focused treatments are of higher priority than strategic/proactive toxicology-focused treatments, although both could be implemented in parallel to reinforce each other. However, for long-term pandemic prevention, toxicology-based approaches should be given higher priority than virology-based approaches. Since current COVID-19 treatments globally ignore the toxicology component almost completely, only limited benefits can be expected from these treatments.